2020
DOI: 10.1080/10255842.2020.1777546
|View full text |Cite
|
Sign up to set email alerts
|

The influence of musculoskeletal forces on the growth of the prenatal cortex in the ilium: a finite element study

Abstract: Remodelling and adaptation of bone within the pelvis is believed to be influenced by the mechanical strains generated during locomotion. Variation in the cortical bone thickness observed in the prenatal ilium has been linked to the musculoskeletal loading associated with in utero movements; for example the development of a thicker gluteal cortex is a possible response to contractions of the gluteal muscles. This study examines if the strains generated in the prenatal iliac cortex due to musculoskeletal loading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Mechanical loading triggered the mechanoregulation of bone to reach mechnostat with optimal structure to react the surrounding mechanical environment. 23 The substantial asymmetry between left and right femurs revealed by Laumonerie's study 24 suggested unbalanced mechanical loads to be transferred to bilateral ilia via the acetabulum and sacroiliac joint. 25 , 26 Moreover, muscles and ligaments surrounding the ilia engage in a gait pattern, which may present asymmetrical features.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanical loading triggered the mechanoregulation of bone to reach mechnostat with optimal structure to react the surrounding mechanical environment. 23 The substantial asymmetry between left and right femurs revealed by Laumonerie's study 24 suggested unbalanced mechanical loads to be transferred to bilateral ilia via the acetabulum and sacroiliac joint. 25 , 26 Moreover, muscles and ligaments surrounding the ilia engage in a gait pattern, which may present asymmetrical features.…”
Section: Discussionmentioning
confidence: 99%
“…As the load‐bearing site, the ilia could have an active mechanobiology‐related bone modeling and remodeling process. Mechanical loading triggered the mechanoregulation of bone to reach mechnostat with optimal structure to react the surrounding mechanical environment 23 . The substantial asymmetry between left and right femurs revealed by Laumonerie's study 24 suggested unbalanced mechanical loads to be transferred to bilateral ilia via the acetabulum and sacroiliac joint 25,26 .…”
Section: Discussionmentioning
confidence: 99%